2018
DOI: 10.1111/apa.14668
|View full text |Cite
|
Sign up to set email alerts
|

Social‐emotional problems among three‐year‐olds differ based on the child's gender and custody arrangement

Abstract: Aim The aim of this study was to investigate mental health with respect to social‐emotional problems among three‐year‐olds in relation to their gender, custody arrangements and place of residence. Methods A cross‐sectional population‐based design was used, encompassing 7179 three‐year‐olds in northern Sweden during the period 2014–2017 from the regional Salut Register. Descriptive and comparative analyses were performed based on parents’ responses on the Ages and Stages Questionnaires: Social‐Emotional, supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Children who did not live with both parents were more likely to be at risk, especially girls. We have discussed this finding in detail in our previous publication (7). The same applies to the gender differences we found.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Children who did not live with both parents were more likely to be at risk, especially girls. We have discussed this finding in detail in our previous publication (7). The same applies to the gender differences we found.…”
Section: Discussionsupporting
confidence: 70%
“…The first edition of the ASQ:SE 36-month interval was included in the questionnaire used in this study (1,21). The ASQ:SE reflects the risk of social-emotional problems among children and it is considered to have adequate psychometric properties that includes validity and reliability internationally (7,(21)(22)(23). ASQ:SE consists of 31 items and three open-ended questions, the latter not used in this study.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Previous study on the distribution of the ASQ:SE items [10] has shown that parents were mainly concerned about the following items: children's eating situation, problems when asked whether the child checks that you are nearby, does what you ask him/her, complies with your requests, cries or screams for a long time, or about a child's hyperactivity. Although many children may have difficulties in these areas, it does not necessarily mean that they should be considered having social-emotional problems.…”
Section: Items That Contributed To High Levels Of Social-emotional Problemsmentioning
confidence: 99%
“…Gender differences have been identified in children's social and behavioural problems. Pre-school aged boys have significantly more externalizing behaviour, depression and developmental disorders compared to girls [7][8][9][10]. Early childhood is an important period for measuring and detecting mental health problems, and use of a screening instrument can aid early detection of children's behavioural delays or disorders in order to enable early interventions suitable for both boys and girls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation